Disparitas Perlindungan Hak Tersangka pada Penyidikan Pidana Militer dan Umum di Indonesia dalam Perspektif Keadilan Prosedural - Antariksa Irawan; Ujuh Juhana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
Indonesia adopts a dual criminal justice system that differentiates the standards of protection for suspects' rights between the general and military justice systems. The enactment of the new Criminal Code (KUHP) and Criminal Procedure Code (KUHAP) has strengthened the protection of civil rights, while military criminal procedure continues to be governed by Law Number 31 of 1997, resulting in disparities that may conflict with the principle of equality before the law. This study aims to comparatively analyze the standards of protection for suspects' rights during the investigation stage in both systems based on the principle of justice. The study employed a normative juridical method using statutory, comparative, and conceptual approaches. The primary legal materials consisted of Law Number 1 of 2023, Law Number 20 of 2025, Law Number 31 of 1997, and the 1945 Constitution of the Republic of Indonesia. The analysis was conducted using Rawls' Theory of Procedural Justice. The findings indicate that investigations within the general criminal justice system have fulfilled the principles of procedural justice through the expansion of pretrial review and the provision of legal assistance from the outset. In contrast, military criminal investigations remain constrained by the dominance of command authority, restrictions on the role of legal counsel, and the absence of external judicial oversight. Therefore, a revision of Law Number 31 of 1997 is necessary to ensure a fair trial.